Existence Of Agreement In Foreign Language In The Process Of Verification In The Court - Yuhelson, Yuhelson; Sinaulan, Ramlani Lina; Utoyo, Bambang (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2020)
In line with the increasingly waning of the State borders in trade and business, then currently many trade and business agreements in Indonesia are made or entered into inforeign languages. The law has in principle governed the language of the agreement, in which the Law requires the use of the Indonesian language as the primary language of the agreement, while the secondary language may use language understood by those who do not understand the Indonesian language. The problems a rise when the parties to the agreement do not understand the language arrangements provided for by this law and use Foreign languages as the primary language even further as the only language used in an agreement. This is certainly contrary to the provisions of the law and vulnerable to create new legal problems. The method used is jurical normative, amethod that examines the application of principles or norms in positive law, which examines the legal force of agreement made in private form in a foreign language. The data used are secondary data consisting of primary, secondary and tertiary legal materials. With regard to data analysis was done by using juridical qualitative analysis method. The legal theory used is the legal certainty theory according to Jan Michiel Otto and Substantiation Theory. The results of this study is an agreement made or entered into ina foreign language has no legal substantiation before a Courtof law as they are contrary to the provisions of Article 31 of Law Number 24 of 2009. There fore the legal consequences of an agreement made in private form in a foreign language is considered to be null and void, and as a consequence, such agreement is considered never to exist.